I'm doing Problem II.3.4 in textbook Analysis I by Amann/Escher.

enter image description here

After elementary transformations, the problem is equivalent to the below theorem:

Theorem: For $x_0 \ge 1$, the sequence $(x_n)$ defined recursively by $x_{n+1} = (x_n +1/x_n)/2$ converges to $1$.

Could you please verify whether my attempt is fine or contains logical gaps/errors? Any suggestion is greatly appreciated!

My attempt:

First, we prove that this sequence is convergent. By AM-GM inequality, $x_{n+1} = (x_n +1/x_n)/2 \ge 1$ for all $n$, so the sequence is bounded from below. We have $x_{n+1} - x_n = (1-x_n^2)/(2x_n) \le 0$ and thus the sequence is decreasing. As such, $\lim_{n \to \infty} x_n =a \in \mathbb R^+$.

Next, we prove that $a=1$. We have

$$\begin{aligned}a &= \lim_{n \to \infty} x_n &&= \lim_{n \to \infty} x_{n+1} \\ &= \lim_{n \to \infty} (x_n +1/x_n)/2 &&= \left ( \lim_{n \to \infty} x_n + \dfrac{1}{\lim_{n \to \infty} x_n} \right)/2 \\ &=(a+1/a)/2 \end{aligned}$$

This equation implies $a=1$. This completes the proof.


Your proof is fine. You showed that the sequence is decreasing and bounded below (thus convergent). You might elaborate that the equation $a = (a+1/a)/2$ has two solutions ($a= \pm 1$), but only $a=1$ can be the limit.

Alternatively observe that $$ 0 \le x_{n+1} - 1 = \frac{(x_n-1)^2}{2x_n} \le \frac{(x_n-1)^2}{2} $$ which also implies convergence $x_n \to 1$.

  • $\begingroup$ Your proof is much more elegant. Thank you so much ;) $\endgroup$
    – Akira
    Aug 21 '19 at 5:36

Just a hint:

With $y = \frac{1}{2}( x + a/x)$ we have $$y \pm \sqrt{a} = \frac{(x\pm \sqrt{a})^2}{2 x}$$ so $$\frac{y-\sqrt{a}}{y+\sqrt{a}}= \left(\frac{x-\sqrt{a}}{x+\sqrt{a}}\right)^2$$

Now we are reduced to investigating the recurrence $$y_{n+1}= y_n^2$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.